Financial Analysis of Irrigation Method Using Micro sprayer Application for Paddy Field Tobacco (Nicotiana tabaccum) on Madura - Kurniati, Evi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
Tobacco farming supported 70-80% of yearly farmer’s income. Irrigation system application to tobacco was to reduced worker and increased the efficiency of water use so could reach the quality and quantity of tobacco. As a new technology, it was expensive so that financial analysis is needed in order to know the feasibility of the technology. There were no influenced from watering method application to tobacco’s productivity, quality index and farmer’s income, but gave an influenced to tobacco’s quality (Sugar/Nicotine ratio). The financial analysis showed that Micro sprayer Irrigation were not feasible to be applied on paddy field tobacco on Madura because the NPV was under zero and the B/C ratio was under 1. Keywords: micro sprayer, irrigation method, tobacco